Development, validation, and usability testing of prototype mobile application for oral health promotion during pregnancy in India - Chaity Sarkar; Vikrant Mohanty; Aswini Y Balappanavar; Kavita Rijhwani; Puneet Chahar (Wolters Kluwer Medknow Publications, 2023)
Background: Oral diseases are a silent epidemic. Objectives: The objectives of the study were to develop, validate, and assess the usability of an oral health prototype mobile application for oral health promotion among pregnant women in India. Materials and Methods: A cross-sectional study was conducted in Tertiary Care Hospital in Delhi, India, after obtaining Ethical Clearance from the Institutional Ethical Committee Board. The study was conducted in three phases: development of the prototype app, its validation, followed by usability testing of the app. Mobile app was validated by 30 pregnant women and 30 subject experts using Heuristic Analysis Scale and usability testing by 30 pregnant women based on System Usability Scale (SUS). Data were analyzed with IBM SPSS version 21.0. Results: Majority (over 90%) of pregnant women and subject experts strongly acknowledged that the app educated the users using positive motivation strategies, instilling comprehensive knowledge and faced no issues with the appropriate functionality of the app. The prototype app scored 73.75 on SUS, indicating high usability. Conclusion: This study holistically explored various dimensions of oral health care in pregnant women. Its novelty is proven by the fact that the content of the prototype application has been phase wise developed and validated by pregnant women and subject experts. Usability testing of the app indicated its high acceptability and ease of use among pregnant women in India.